2016
DOI: 10.1038/srep33696
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces of soil bacterial community structure, diversity, and function in temperate grasslands and forests

Abstract: Soil bacteria provide a large range of ecosystem services such as nutrient cycling. Despite their important role in soil systems, compositional and functional responses of bacterial communities to different land use and management regimes are not fully understood. Here, we assessed soil bacterial communities in 150 forest and 150 grassland soils derived from three German regions by pyrotag sequencing of 16S rRNA genes. Land use type (forest and grassland) and soil edaphic properties strongly affected bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
197
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(228 citation statements)
references
References 56 publications
25
197
4
2
Order By: Relevance
“…14.7 % a exploratory studies on forest-soil microorganisms observed a stronger effect of the dominant tree species than of the SMI on the microbial community (Goldmann et al, 2015;Kaiser et al, 2016;Purahong et al, 2014); only one study on litter decaying fungi and bacteria indicated a significant difference between natural and managed beech forests (Purahong et al, 2015). Kaiser et al (2016) discussed that the different tree species influence soil bacteria by shifting the pH in soil; hence, tree species was designated as the main predictor for bacterial community composition. However, the bulk soil pH did not differ significantly between beech and pine forest in Schorfheide-Chorin (Table 1); hence, the algae in BSCs were not affected by this abiotic parameter.…”
Section: Correlation With Smimentioning
confidence: 99%
“…14.7 % a exploratory studies on forest-soil microorganisms observed a stronger effect of the dominant tree species than of the SMI on the microbial community (Goldmann et al, 2015;Kaiser et al, 2016;Purahong et al, 2014); only one study on litter decaying fungi and bacteria indicated a significant difference between natural and managed beech forests (Purahong et al, 2015). Kaiser et al (2016) discussed that the different tree species influence soil bacteria by shifting the pH in soil; hence, tree species was designated as the main predictor for bacterial community composition. However, the bulk soil pH did not differ significantly between beech and pine forest in Schorfheide-Chorin (Table 1); hence, the algae in BSCs were not affected by this abiotic parameter.…”
Section: Correlation With Smimentioning
confidence: 99%
“…13 Similar results were reported in a study of bacterial communities in German grassland and forest soils. 14,15 In a more recent study, both bacterial and fungal communities exhibited contrasting beta diversity among two types of European subalpine/alpine grasslands, and both bacterial and fungal communities were influenced by grassland type. 16 However, most of these studies have been conducted in temperate northern hemisphere grasslands and none is directly relevant to the unique and defined biomes of South Africa.…”
Section: Introductionmentioning
confidence: 97%
“…Soil texture also strongly affects microbial community compositions, largely through the effects of particle size on nutrients, habitat space, moisture, and redox levels (Kaiser et al, 2016). Molineux et al (2017) showed, the effectiveness and persistence of microbial inocula on green roofs differed according to whether or not the substrate was concrete or brick based.…”
Section: Are Some Growing Media More Conducive To the Maintenance Of mentioning
confidence: 99%